Keamanan Maritim di Laut Cina Selatan: Tinjauan atas Analisa Barry Buzan - Setiawan, Asep (Jurnal Keamanan Nasional, 2017)
The article discusses maritime security in the South China Sea based on the security concept by Barry Buzan. According to Buzan, the analysis of security is divided into three levels: individual, national, and international. In addition, the security dimension consists of military security, politics, society, economics, and the environment. Maritime security can be seen as the combination of preventive and responsive measures to protect the maritime domain against threats and intentional unlawful acts. With this concept, maritime security in South China Sea considers three-level analyses and at the same time involves multiple dimensions of security factors. Security in the area should be put in the correct perspective to get a full understand of the complexity of this matter.